The Experiences of Post-Separation Survivors of Domestic Violence During the Covid-19 Pandemic: Findings From a Qualitative Study in the United Kingdom - Desai, Ruchi (Violence against women, 2024)
Post-separation for domestic violence (DV) survivors is known to be a period of heightened risk of domestic homicide. Evidence points to increased rates of DV during the Covid-19 pandemic, with specific challenges in help-seeking from DV services, yet studies that capture this qualitatively are still emerging. This UK study investigated the experiences of 21 separated DV survivors (all women) during the Covid-19 pandemic. Inductive, thematic analysis highlighted participants’ psychological distress, isolation, fear of Covid-19 transmission, and detachment from support networks. The findings reflect the interconnected nature of adversities experienced by DV survivors and the exacerbation of these due to the insidious, multifaceted, and synergistic impacts of DV and the pandemic.